The Language of Othering in a Diverse Europe - Falkowska, Marta,; Linde-Usiekniewicz, Jadwiga, (Brill's Studies in Language, Cognition and Culture ;, 2025)
This book explores how language is used to create division and discrimination in diverse European societies by emphasizing differences in ethnicity, race, national identity, beliefs, or appearance. The authors analyze how public discourse-particularly in political and media narratives-shapes and reinforces an "us vs. them" mindset. They examine words and expressions that denigrate or marginalize specific groups in Polish, German, Czech, Slovak, and Croatian, and observe how certain communities are also reclaiming terms that were once hurtful. The analyses of linguistic strategies employed in the process of othering demonstrate that the concept of othering can be effectively applied to linguistic data. Contributors are: Dagmara Banasiak, Marta Chojnacka-Kuraś, Marta Falkowska, Jadranka Gvozdanović, Milena Hebal-Jezierska, Agnieszka Karlińska, Anna Kołos, Marie Kopřivová, Marek Łaziński, Jadwiga Linde-Usiekniewicz, Agnieszka Mikołajczuk, Iva Petrak, Jiří Rejzek, Lucie Saicová Římalová, Łukasz Wnuk, and Magdalena Zawisławska.